Desarrollo del módulo de gestión de proyectos de investigación en el sistema integrado de gestión de la Universidad Técnica de Cotopaxi. - Pullupaxi Cando, Hector Geovanny (2021)
The Research Direction develops lines, programs and projects of formative and generative research at the Technical University of Cotopaxi. The documentation on formative research projects is stored physically and digitally; digital through file hosting services on the Internet, which makes it difficult to manage and search for information, causing resource consumption and loss of time. The authorities aware of the problem opted for the development of the formative research project management module in the integrated system of the Technical University of Cotopaxi. The module integrates several functionalities: presentation of formative research projects (annex 1) by the teacher / researcher, review of the training project (annex 2) under the responsibility of the Director of the Course and Research Coordinator of the Faculty, evaluate compliance with the evaluation criteria of the training project (annex 3) of obligation of the Director of the Career and Research Coordinator of the Faculty. The development of the module involved the use of the SCRUM methodology, the .Net Framework development environment with the C # programming language, the Microsoft SQL Server 2012 database manager, Visual Studio Enterprise 2015.